Biochemical and Microbiological Quality of Smoked Channa punctatus available in Manipur - H., Lilabati; N., Bijayanti; W., Viswanath (Fishery Technology, 2025)
A comparative study on the biochemical and microbiological quality of the smoked freshwater snakehead (Channa punctatus) of Manipur (A) and smoked Channa punctatus brought from other states (B) has been made. ’A’ has more smoky odour, higher reconstitution property, total protein, lipid, ash, NFN, pH than that of ’B’ . Total bacterial (TBC) and fungal (TFC) counts were higher in ’A’. While ’A’ did not have coagulase positive staphylococcus and faecal Streptococci, the two were detected from ’B’. In both the samples, E. coli and Salmonella were not detected. Xanthomoms and Penicillium sp. were dominant in ’A’ and Bacillus, Micrococcus and Aspergillus sp. in ’B’.